IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DALAM PENCEGAHAN STUNTING DI KECAMATAN KRUENG BARONA JAYA KABUPATEN ACEH BESAR - Humaira, Humaira; Lensoni, Lensoni; Putri, Rosalia (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
Implementation is the act of implementing a scheme that has been carefully prepared to carry out development administration policies so that the process achieves the desired results. The purpose of this research is to describe how the Village Fund Allocation Policy is implemented in efforts to prevent stunting in Krueng Barona Jaya District, Aceh Besar District. One of the stunting management programs carried out by the village government is the provision of supplementary food (PMT). This program is provided through the village budget which prioritizes pregnant women, toddlers and the elderly. This type of research was carried out using qualitative research methods with a descriptive approach. This research obtained the result that the stunting management program originating from the village income and expenditure budget (APBDD) had been implemented in villages in Krueng Barona Jaya District. Conclusion The implementation of the Village Fund Allocation (ADD) Policy in Krueng Barona Jaya District in an effort to prevent stunting is running quite smoothly. This can be seen from the results of the preparatory stage of interviews in the form of preparing a List of Proposed Activity Plans (DURK), the completion of each activity up to the stage of preparing accountability.